Population Pharmacodynamics of IPX066: An Oral Extended‐Release Capsule Formulation of Carbidopa–Levodopa, and Immediate‐Release Carbidopa–Levodopa in Patients With Advanced Parkinson's Disease. (20th February 2013) - Mao, Zhongping; Hsu, Ann; Gupta, Suneel; Modi, Nishit B.
Abstract A pharmacodynamic model is presented to describe the motor effects (tapping rate, Unified Parkinson's Disease Rating Scale [UPDRS] Part III, and investigator‐rating of ON/OFF, including dyskinesia) of levodopa (LD) in patients with advanced idiopathic Parkinson's disease (PD) treated with immediate‐release (IR) carbidopa–levodopa (CD–LD) or an extended‐release (ER) formulation of CD–LD (IPX066). Twenty‐seven patients participated in this open‐label, randomized, single‐ and multiple‐dose, crossover study. The pharmacodynamic models included a biophase effect site with a sigmoid Emax transduction for tapping and UPDRS and an ordered categorical model for dyskinesia. The pharmacodynamics of LD was characterized by a conduction function with a half‐life of 0.59 hours for tapping rate, and 0.4 hours for UPDRS Part III and dyskinesia. The LD concentration for half‐maximal effect was 1530 ng/mL, 810 ng/mL, and 600 ng/mL for tapping rate, UPDRS Part III, and dyskinesia, respectively. The sigmoidicity of the transduction was 1.53, 2.5, and 2.1 for tapping rate, UPDRS Part III, and dyskinesia, respectively. External validation of the pharmacodynamic model using tapping rate indicated good performance of the model.